Recent advances in highly integrated energy conversion and storage system. Issue 2 (28th April 2022) - Shao, Changxiang; Zhao, Yang; Qu, Liangti
Abstract : High integration is the inevitable development trend of the next‐generation intelligent power system. The review presents four integration modes of power systems that combine energy conversion and storage devices, focuses on summarizing and analyzing the all‐in‐one power system with the highest integration degree based on different energy sources. It is expected to provide reference and guidance for future investigation.